Differentiable semigroups are Lie groups - John P. Holmes; Mitch Anderson (International Journal of Mathematics and Mathematical Sciences)
We present here a modern, detailed proof to the following theorem which was introduced by Garrett Birkhoff [1] in 1938. If S is a local semigroup with neighborhood of 1 homeomorphic to a Banach space and with multiplication strongly differentiable at 1, then S is a local Lie Group. Although this theorem is more than 50 years old and remains the strongest result relating to Hilbert's fifth problem in the infinite dimensional setting, it is frequently overlooked in favor of weaker results. Therefore, it is the goal of the authors here to clarify its importance and to demonstrate a proofwhich is more accessible to contemporary readers than the one offered by Birkhoff.